Faktor yang Mempengaruhi Minimnya Literasi Siswa SD - Husnil Khatimah; M. Milpa Sastra Wardana; Salmaini Safitri Syam; Nur Azmi Alwi (Lembaga Pengembangan Kinerja Dosen, 2025)
The literacy level of primary school-age children in Indonesia is still relatively low, which has an impact on children's academic ability and cognitive development. This study aims to identify and analyze the factors that influence the lack of literacy in primary school-age children. The method used was literature study and field observation with a qualitative approach. The results show that low literacy is caused by several main factors, namely the lack of reading habits at home, limited facilities and interesting reading materials, less varied learning methods, and the minimal role of teachers and parents in fostering interest in reading. In addition, the influence of technological developments also plays a role in diverting children's attention from reading activities. The conclusion of this study emphasizes the importance of collaboration between schools, families and communities in creating an environment that supports an early literacy culture.